Habilidades socioemocionales y su incidencia en el rendimiento académico de los estudiantes de octavo año de educación básica de la Unidad Educativa Guare del cantón Baba Provincia de Los Ríos periodo académico 2024 -2025 - Vinces Cardenas, Domenica Gricel (2025)
The general objective of this curricular integration work was to determine the incidence of social-emotional skills in the academic performance of eighth grade students of the Guare Educational Unit of the Baba canton, Los Ríos province, academic period 2024 -2025. For this purpose, a descriptive methodology was implemented, with a mixed approach and a non-experimental design. Therefore, it was necessary the application of an interview directed to teachers, a survey implemented to students through a test as an instrument of data collection and an observation sheet, to verify the answers given by the subjects of study and to evaluate the incidence between the variables of study in their natural context. The results obtained showed that the highest percentage of students in 8th grade of EGB parallel A and B, had a Resolute level of socioemotional development, that is, an acceptable level in terms of mastery and control of emotions, ease of relating and working in a team. Not so, the second highest percentage, which evidenced a Receptive level, have difficulty in managing the aforementioned skills. The findings revealed that intrapersonal, interpersonal and cognitive skills have a very significant impact on the fundamental aspects that affect students' academic performance. Thus, those individuals who have a high level of socioemotional development have greater opportunities for success in their personal, holistic and integral formation.